Tailoring Light–Matter Interactions in Overcoupled Resonator for Biomolecule Recognition and Detection - Dongxiao Li; Hong Zhou; Zhihao Ren; Cheng Xu; Chengkuo Lee (Nano-Micro Letters)
Highlights Proposed a new paradigm for nanoantenna design using coupled-mode theory. Designed an OC-Hµ resonator with excellent sensing performance. Using OC-Hµ resonators for biomolecule recognition and detection.